Continuing Vocational Training in Germany : a comparative study using 3 German Data Set - Kuckulenz, Anja [Verfasser] (Zentrum für Europäische Wirtschaftsforschung, 2006)
"Empirical work on continuing training in Germany provides surprisingly divergent evidence on the incidence of training. This makes comparison of econometric analyses of the impact of training on labour market outcomes difficult. Three large German data sets are used here to bring to light the data issue concerning continuing training. Differences in the defnition and consequences for economic research are discussed. In detail, training incidence, determinants of training and the correlation between continuing vocational training and wages are examined. Results are compared in order to analyse in how far differences in estimated wage effects of continuing vocational training are due to the data set used and to how the training variable is set up." (Autorenreferat, BIBB-Doku)
ftp://ftp.zew.de/pub/zew-docs/dp/dp06024.pdf [Zugriff: 19.3.2008]
Keywords: S 1.5.2 Berufliche Weiterbildung; S 4.3.6 Human Capital; I 2.1 Deutschland; Bildungsökonomie; Berufliche Weiterbildung; Beschäftigungseffekte; Einkommenseffekte; Einflussfaktor; Empirische Forschung; Bundesrepublik Deutschland